Recurrent KRAS mutations in papillary renal neoplasm with reverse polarity - Al-Obaidy, Khaleel I.; Eble, John N.; Nassiri, Mehdi; Cheng, Liang; Eldomery, Mohammad K.; Williamson, Sean R.; Sakr, Wael A.; Gupta, Nilesh; Hassan, Oudai; Idrees, Muhammad T.; Grignon, David J. (Modern pathology, 2020)
We recently proposed that an epithelial renal tumor “papillary renal neoplasm with reverse polarity” represents a distinct entity. It constituted 4% of previously diagnosed papillary renal cell carcinoma at the participating institutions. Histologically, it is characterized by papillary or tubulopapillary architecture covered by a single layer of eosinophilic cells with finely granular cytoplasm and apically located nuclei. It is characteristically positive for GATA3 and L1CAM and lack vimentin and, to a lesser extent, α-methylacyl-CoA-racemase (AMACR/p504s) immunostaining. To investigate the molecular pathogenesis of these tumors, we performed targeted next-generation sequencing on ten previously reported papillary renal neoplasms with reverse polarity, followed by a targeted polymerase chain reaction analysis for KRAS mutations in a control series of 30 type 1 and 2 papillary renal cell carcinomas. KRAS missense mutations were identified in eight of ten papillary renal neoplasms with reverse polarity. These mutations were clustered in exon 2—codon 12: c.35 G > T ( n = 6) or c.34 G > C ( n = 2) resulting in p.Gly12Val and p.Gly12Arg alterations, respectively. One of the wild-type tumors had BRAF c.1798_1799delGTinsAG (p.Val600Arg) mutation. No KRAS mutations were identified in any of the 30 control tumors. In summary, this study supports our proposal that papillary renal neoplasm with reverse polarity is an entity distinct from papillary renal cell carcinoma and the only renal cell neoplasm to consistently harbor KRAS mutations.